CM-10 Histopathological, Serological and Molecular Confirmation of APMV- 1 Infection - I Gusti Agung Arta Putra; Anak Agung Ayu Mirah Adi (Media Veteriner, 2015)
Histopathological, Serological and Molecular Confirmation of APMV- 1 Infection